Respon Tiongkok Terhadap Perkembangan Teknologi Antariksa Amerika Serikat Pada Tahun 2018-2021 - Pramadita, Kadek Windy; Widya Nugraha, A.A. Bagus Surya; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study aims to see China's response to the increasing capabilities of the United States' space technology. Even though it has been stated in the Outer Space Treaty, United States under the leadership of Donald Trump has formed a special force of space areas, namely the United States Space Force with aims to remaining the United States dominance in the space area. China then responded to this because China did not want a dominating power in the space area. This study used qualitative research methods. The framework used in this study is the Balance of Power on the concept of Neo Realism, to see the causality of China's response to the increasing capabilities of United States space technology which is considered as a threat. In this study, it was found that China give responded in three ways, first by increasing its own space technology capabilities. Second by activating its own navigation system, namely Beidou so China will not depend on US GPS, and third collaborating with Russia to form ILRS, so China would no longer depend on ISS. In conclusion we can see China's responses is to balance the power of US space capabilities, so there’s no power dominates in the space area.